Social Dynamics and Tourist Experience at Wakila Peak, Muna Island: A Sociology of Tourism Perspective - Muhammad Obie (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyze the social dynamics and tourist experiences at Peak Wakila Peak, Muna Island, from a sociological perspective on tourism. Method: This study uses a qualitative case study design, with field observations, in-depth interviews with visitors and local actors, and documentation of tourism activities. Result: Wakila Peak serves not only as a recreational destination but also as a social space that facilitates interaction, collective identity formation, and the production of experiential tourism meaning. The tourist experience is shaped by a combination of natural landscapes, social practices, and symbolic interactions among visitors that strengthen the destination’s appeal. Contribution: Theoretically, this research contributes to the sociology of tourism by positioning the tourist experience as a dynamic social construction within the context of local destinations. The practical implication of this study is the importance of strengthening community-based tourism management that considers social and cultural aspects as integral to sustainable destination development.